Paroxysmal spinal hemidystonia in neuromyelitis optica. Issue 8 (16th August 2022) - Gutti, Nagendra B.; Kalita, Jayantee; Pandey, Prakash C.
Abstract: Paroxysmal dystonia occurs because of genetic or structural lesion in the basal ganglia or thalamus, and there is paucity of reporting in spinal pathology. We report a patient with paroxysmal hemidystonia admitted to a tertiary care hospital, India, and review the literature on spinal dystonia in neuromyelitis optica (NMO). A 19‐year‐old woman presented with recurrent visual loss and quadriparesis. She developed paroxysmal hemidystonia after 18 days of a second episode of quadriplegia, during which her muscle power improved to Grade 3. Magnetic resonance imaging (MRI) of her spine showed central T2 hyperintensity extending from C2 to C7 vertebral level, and a cranial MRI was normal. Tibial somatosensory evoked potentials were unrecordable. Aquaporin‐4 antibody was positive in serum, confirming the diagnosis of NMO. Paroxysmal hemidystonia responded to carbamazepine 200 mg thrice daily. Paroxysmal dystonia may occur in a patient with myelitis and may respond to carbamazepine.